Design and implementation of smart home system based on IoT - Yinyan Chen; Hong Zhang; Shijie Zhong (Results in Engineering)
With the continuous development of Internet of Things technology and AI technology, a new generation of smart home systems is being promoted. Traditional smart home devices are complex to operate, resulting in high learning costs. They also lack security and reliability, and cannot guarantee the use and safety of the elderly and children, limiting their popularity. This system is based on ATMEGA2560 and IoT to design and implement a smart home system suitable for people of all ages. It solves complex operation problems through voice control, solves safety problems through fall detection, GPS positioning and light alarm control, and improves reliability through intelligent remote control. In addition, the system can sense fire, hazardous gases, and earthquakes and sound an alarm. The system reduces CPU occupancy time by changing the writing mode of the display module, thereby reducing the system's requirements for the processor and reducing the processor cost. In image processing, by recording a large number of faces, the recognition accuracy can be improved, the requirements and costs of image processing chips can be reduced, and low-cost remote video monitoring can be achieved.